2001
DOI: 10.1093/geronb/56.4.s195
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Mortality Among Black and White Adults: Examining the Dynamic Evaluation Thesis

Abstract: The results suggest that self-ratings of health are sensitive to declines in physical health, especially those associated with terminal drop. The analysis also demonstrates the importance of using dynamic models for studying the link between self-rated health and mortality if data from multiple observation points are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
172
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(187 citation statements)
references
References 42 publications
9
172
1
5
Order By: Relevance
“…However, our findings that selfrated health only moderately correlated with medical diagnoses and psychological distress support claims that self-rated health is a cognitive representation or perception of health. [16][17][18] We also found that patients who perceived dissatisfying family support and who rated their health status as poor reported the most psychological distress on the SCL-10 and GHQ-12. However, participants with satisfying family support, regardless of their self-rated health, reported little psychological distress.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, our findings that selfrated health only moderately correlated with medical diagnoses and psychological distress support claims that self-rated health is a cognitive representation or perception of health. [16][17][18] We also found that patients who perceived dissatisfying family support and who rated their health status as poor reported the most psychological distress on the SCL-10 and GHQ-12. However, participants with satisfying family support, regardless of their self-rated health, reported little psychological distress.…”
Section: Discussionmentioning
confidence: 66%
“…Self-rated health is a dynamic representation of overall health that includes the patient's knowledge of current and past medical problems, current frailty, and health changes over time. [16][17][18] Because self-rated health is often measured with a single item, it is an easily administered assessment tool in clinic settings. Poor self-rated health is related to an increased risk of mortality, even when a variety of health indicators are controlled for.…”
Section: Self-rated Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[25][26][27][28][29] The degree by which SRH reflects psychological distress 25 and chronic medical and mental disorders 1,2,12-14 may differ from one ethnic group to another. [30][31][32][33][34][35][36] The meaning and determinants of SRH are not universal, but population specific. 12,26,28 Factors associated with SRH also vary across diverse ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…12,26,28 Factors associated with SRH also vary across diverse ethnic groups. [30][31][32][33][34][35][36] As a general rule, poor SRH better reflects health problems in non-Hispanic Whites compared to all ethnic minorities such as Blacks, Hispanics, and Asians. 12 Poor SRH also better predicts mortality in Whites than non-Whites.…”
Section: Introductionmentioning
confidence: 99%